The Discriminatory Function of Some Physical and Kinetic Abilities in Performing the Skill of Rising in the Back Rotation to Focus on Pull Up (International Journal of Psychosocial Rehabilitation, 2020)
Gymnastics is an aspect of physical activity. It is characterized by its comprehensive effect on the muscle groups, as well as its good effect on the rest of the other body systems in order to achieve harmony, complementarity and balanced growth Which is the basis of integrating mental processes, and this is apart from other qualities like body flexibility, consistency, agility, muscle strength, and self-confidence. Physical and kinetic abilities are the basis of physical education, which enables the individual to perform the movements well and within a framework characterized by smooth and consistent performance, and having the individual possess these physical and kinetic qualities will help him learn and perform systematic skills in the shortest time.